Provisional Agenda for the Twenty-Fourth Meeting of the International Monetary and Financial Committee (IMFC). (Policy Papers; Policy Paper, 2011)
Provisional Agenda 1. Adoption of Agenda-Opening Remarks by the Chair 2. The Managing Director's Consolidated Multilateral Surveillance Report - Presentation by the IMF Economic and Financial Counsellors The Managing Director's Action Plan - Presentation by the Managing Director 3. Approval of Press Communique.